2012
DOI: 10.1183/09031936.00137211
|View full text |Cite
|
Sign up to set email alerts
|

Does oxidative stress modulate limb muscle atrophy in severe COPD patients?

Abstract: Oxidative stress may differentially regulate protein loss within peripheral muscles of severe chronic obstructive pulmonary disease (COPD) patients exhibiting different body composition.Oxidation levels of proteins, myosin heavy chain (MyHC) and myonuclei, superoxide anion, antioxidants, actin, creatine kinase, carbonic anhydrase-3, ubiquitin-proteasome system, redoxsignalling pathways, inflammation and muscle structure, and damage were quantified in limb muscles of severe COPD patients with and without muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
226
4
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 133 publications
(247 citation statements)
references
References 45 publications
15
226
4
2
Order By: Relevance
“…Additionally, limb muscle NEDD4 protein expression is increased in patients with COPD 57. Total poly‐ubiquitinated protein is increased in limb muscles of COPD patients compared with healthy controls39, 56 and in cachectic COPD patients compared with non‐cachectic COPD patients 38…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 95%
See 4 more Smart Citations
“…Additionally, limb muscle NEDD4 protein expression is increased in patients with COPD 57. Total poly‐ubiquitinated protein is increased in limb muscles of COPD patients compared with healthy controls39, 56 and in cachectic COPD patients compared with non‐cachectic COPD patients 38…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 95%
“…MURF1 limb and respiratory muscle mRNA and protein expression appear unaltered in COPD patients compared with controls,38, 40, 55, 56, 57 although one study reported increased MURF1 protein expression in the limb muscles of cachectic COPD patients 39. In COPD patients, MURF1 protein expression is relatively increased in limb muscle than in the respiratory muscle, while this difference was not found in controls 46.…”
Section: New Insights In the Pathophysiology Of Muscle Wasting In Chrmentioning
confidence: 96%
See 3 more Smart Citations